Comparison Of Osteoprotegrin And Estradiol Levels In Iraqi Women With Osteoporosis And Women With Osteopenia (Journal of the College of Basic Education, 2025)
Osteoporosis is a common bone disease, especially in women after menopause and with aging, where bones become more fragile due to decreased density and structural changes. This condition is closely linked to a decline in estrogen levels, leading to accelerated bone loss due to an imbalance between bone-forming cells (osteoblasts) and bone resorbing cells (osteoclasts).With aging and the decline in estrogen levels after menopause, caused by the cessation of egg production in the ovaries, the production of inflammatory factors such as interleukin-1 (IL-1), interleukin-6 (IL-6), and tumor necrosis factor (TNF) increases, while the level of the regulatory protein OPG decreases. This imbalance leads to higher bone turnover and osteoporosis. Additionally, it contributes to vascular calcification due to the increased activity of RANKL on bone and vascular cells.Objectives: Evaluate the differences in Osteoprotegerin (OPG) and Estradiol (E2) levels between Iraqi women with osteoporosis and those with osteopenia to determine the impact of these biomarkers on bone health.Method and patients: Three group in this study of population divided into patient group(n=39) seemingly healthy volunteers as control group ,Additionally, 33 women suffered from osteopenia and 34 women suffered from osteoporosis All participants underwent bone mineral density assessment using dual-energy X-ray absorptiometry.Medical examinations, including laboratory tests for women, were conducted at Al-Alwiya Hospital in Baghdad Province, in addition to other tests performed at Al-Wasiti teaching Hospital. Results: The DEXA outcomes revealed osteopenia patients had a higher mean age (49.6 ± 14.17 years) than the control group (42.25 ± 13.13 years), while osteoporosis patients were the oldest (57.47 ± 11.28 years, p = 0.015). Osteoprotegerin levels were highest in the control group (6.47 ± 1.69 ng/ml) and significantly lower in osteopenia (5.56 ± 1.91 ng/ml, p = 0.036) and osteoporosis patients (4.85 ± 1.46 ng/ml, p < 0.001). The decline in osteoprotegerin was more pronounced between healthy individuals and osteopenia patients, while the difference between osteopenia and osteoporosis patients was not significant (p = 0.089). Conclusion: Aging is associated with decreased OPG and estradiol levels, leading to bone imbalance and increased loss. The significant decline from osteopenia to osteoporosis highlights the crucial role of hormonal disturbances in disease progression.